Neural stem cell-derived extracellular vesicles: mini players with key roles in neurogenesis, immunomodulation, neuroprotection and aging - Bonetto, Valentina; Grilli, Mariagrazia (Frontiers in Molecular Biosciences, 2023)
Neural stem/progenitor cells (NSPCs) are self-renewing and multipotent cells of the central nervous system (CNS), where they give rise to neurons, astrocytes and oligodendrocytes both during embryogenesis and throughout adulthood, although only in a few discrete niches. NSPC can integrate and send a plethora of signals not only within the local microenvironment but also at distance, including the systemic macroenvironment. Extracellular vesicles (EVs) are currently envisioned as main players in cell-cell communication in basic and translational neuroscience where they are emerging as an acellular alternative in regenerative medicine. At present NSPC-derived EVs represent a largely unexplored area compared to EVs from other neural sources and EVs from other stem cells, i.e. mesenchymal stem cells. On the other hand, available data suggest that NSPC-derived EVs can play key roles on neurodevelopmental and adult neurogenesis, and they are endowed with neuroprotective and immunomodulatory properties, and even endocrine functions. In this review we specifically highlight major neurogenic and “non neurogenic” properties of NSPC-EVs, the current knowledge on their peculiar cargos and their potential translational value.